Experimental validation of motion sensor Physilog®5 applied to shoulder joint - Jan Krivošej; Jana Garanová Krišťáková; Matej Daniel; Zbyněk Šika (Acta Polytechnica CTU Proceedings, 2023)
The main motivation of this paper is to verify the idea of using the Physilog®5 unit for the patients with shoulder movement difficulties. The attached sensor to the patient’s arm then measures motion during which the patient should follow certain paths. Finally, if a patient has difficulty with motion requirements, some typical pattern for their problem should emerge. By analysing these patterns, a database of typical problems could be created, which could assist doctors in determining a patient’s diagnosis.The experiment is focused on Physilog® concerning the 5th generation. The goal is to experimentally identify and verify the performance of this generation during relatively large motions of the upper limb. For this purpose, an experimental stand representing spherical joint with an accurate absolute position sensing is assembled and calibrated. Subsequently, the three Physilog®5 sensors are mounted on this stand at different positions.